21 Differential Distribution of Modifiable Risk Factors by Socioeconomic Status in Patients Presenting with Acute ST-Segment Elevation Myocardial Infarction. (6th June 2015) - Steele, Lloyd; Lloyd, Amelia; Fotheringham, James; Sultan, Ayyaz; Iqbal, Javaid; Grech, Ever D
Abstract : Background: Lower socioeconomic status (SES) is associated with an increased prevalence of cardiovascular risk factors. Mortality rates from coronary heart disease are higher in low compared to high SES groups. We aimed to assess differences in cardiovascular risk factors by SES in a cohort of patients presenting with acute ST-elevation myocardial infarction (STEMI) undergoing primary PCI. Methods: All patients with acute STEMI undergoing primary PCI in South Yorkshire, England UK between 01/01/2009 and 06/04/2012 were studied. Patient postcodes were used to determine Index of Multiple Deprivation (IMD) values for each patient as an area-level measure of SES. Main results: A total of 1715 acute STEMIs were treated with PCI in 1680 patients during the study period. Smoking status was the only modifiable risk factor distributed incrementally among all SES quartiles (p = 0.001). Smoking prevalence was highest in the most deprived quartile (63.0%) and lowest in the least deprived quartile (25.5%), with a clear gradient (second most deprived 45.8%, second least deprived 38.8%). There were no significant differences in levels of dyslipidaemia (p = 0.107), hypertension (p = 0.651), diabetes (p = 0.868), or mean BMI (p = 0.962). The lowest SES group appeared to smoke more cigarettes per day (19.6 cigarettes per day (18.35–20.77)) and to have smoked for longer (36.7 smoking years (34.64–38.76)) than the highest SES group (17.0 cigarettes per day (13.85–20.24)), 35.9 years (24.43–47.35)), with an observable gradient, although these differences were not statistically significant (p = 0.256 and 0.918, respectively). Conclusion: Smoking was the only modifiable cardiovascular risk factor that showed significant incremental prevalence changes across all SES quartiles (p = 0.001). Targeting smoking prevention strategies at lower income households will be important in reducing health inequalities observed in heart disease mortality rates.